The improvement of leaf rust resistance in selected bread wheat lines - Craven, Maryke (University of the Free State, 2002)
The objective of this study was not only to improve leaf rust (caused by Puccinia triticina) resistance in selected wheats (Triticum aestivum L.), but to focus on durability as well as agronomic acceptability of resistant lines. This was achieved by traditional breeding techniques as well as with the use of AFLP analysis. Seven bread wheat lines were obtained from ARC-Small Grain Institute (SGI) where they were developed. Six leaf rust resistance sources were obtained from the University of the Free State. The breeding strategy focused on creating lines that contained both seedling and adult plant resistance genes. Lr34 was chosen as the adult plant resistance source as it is an important gene due to its durability and interaction with other leaf rust resistance genes. It is also an easy gene to follow as it is associated with leaf tip necrosis. In an attempt to create genotypes that will remain durable, four seedling leaf rust resistance genes (Lr21, Lr32, Lr36 and Lr41) were each combined with Lr34 in the seven SGI backgrounds. By combining seedling and adult plant genes, and selecting only the lowest infection types throughout all phases of testing, a significant shift in the leaf rust resistance of the population occurred. Greenhouse evaluations of plant architecture and agronomic performance of lines containing both a seedling gene and Lr34, indicated that individual plants, similar or better than the original SGI parent, had been selected. Several of these selections can therefore be incorporated in larger, mainstream breeding programmes. It is, however, imperative that the agronomic and quality value of selections be determined under field conditions. More efficient manipulation of an undesignated Lr gene was also attempted. This gene, which originates from T. monococcum, was incorporated in certain bread wheat lines and cultivars. Since the gene is characterized by an immune response to South African pathotypes of leaf rust, it is considered valuable in terms of rust resistance. However, its single gene nature implies it will not remain durable and that it has to be protected in complex resistance gene combinations. To achieve this, linked molecular markers are needed. In this study a putative AFLP marker for leaf rust resistance was generated by S12/M14 and S12/M44 using pooled DNA. Analysis of individual plants from which the DNA bulks were constructed indicated that the marker might not be closely linked to the Lr gene of interest. Validation in three additional backgrounds revealed several instances of recombination between the marker and the gene, emphasising the need to do a proper linkage study. Should the linkage distance be acceptable, the marker might still be useful as it proved to be polymorphic in five different wheat backgrounds. The linkage distance is also needed before the intensive effort to clone and convert the AFLP band to a more user-friendly STS marker will be considered.

Die studie het nie net gefokus op die verbetering van blaarroesweerstand van geselekteerde broodkoringlyne nie, maar op die skepping van volhoubare sowel as agronomies aanvaarbare weerstandstandslyne. Dit is moontlik gemaak deur van tradisionele veredelingstegnieke asook AFLP analises gebruik te maak. Sewe broodkoringlyne is verkry vanaf die LNR-Kleingraaninstituut, waar hulle ontwikkel is. Ses blaarroesweerstandslyne (Triticum aestivum) is van die Universiteit van die Vrystaat verkry. Die veredelingstrategie het gefokus op die inkorporering van beide saailing- en volwasseplantweerstandsgene binne dieselfde lyn. Lr34 is gekies as die geenbron van volwasseplantweerstand aangesien dit, vanweë sy volhoubaarheid en sy interaksie met ander weerstandsgene, 'n baie waardevolle geen is. Verder is Lr34 ook 'n maklike geen om te volg aangesien dit met blaarpuntnekrose geassosiëer word. In 'n poging om lyne te skep wat volhoubare weerstand teen blaarroes sal hê, is vier saailingweerstandsgene (Lr21, Lr32, Lr34 en Lr41) elk afsonderlik met die volwasseplantweerstandsgeen Lr34 gekombineer binne die sewe KGI agtergronde. Deur die kombinering van saailing- en volwasseplantweerstandsgene, asook deur deurlopende selektering vir die laagste infeksietipe gedurende alle evalueringsfases, het daar 'n betekenisvolle verskuiwing in die blaarroesweerstand binne die populasie plaasgevind. Glashuisevaluasies van agronomiese prestasie sowel as planttipe van die onderskeie lyne wat beide 'n saaling- en die Lr34 geen bevat, het aangedui dat individuele plante wat dieselfde, of beter, gevaar het as die oorspronklike KGI ouerlyn, geselekteer is. Verskeie van hierdie seleksies kan dus in die hoofstroomveredelingsprogramme geïnkorporeer word. Dit is egter noodsaaklik dat beide die agronomiese en kwaliteitwaarde van die seleksies onder veldtoestande geëvalueer word. 'n Poging is ook aangewend om 'n onbekende Lr geen te manipuleer. Hierdie geen wat afkomstig is vanaf T. monococcum, is geïnkorporeer in sekere broodkoringlyne. Die geen word as waardevol beskou in terme van roesweerstand, aangesien dit gekarakteriseer word deur 'n immuunreaksie teenoor Suid-Afrikaanse blaarroespatotipes. Weens sy enkelgeenstatus sal die geen egter gou sy volhoubaarheid prysgee. Dit is dus noodsaaklik dat hierdie geen beskerm word binne komplekse weerstandsgeenkombinasies. Om dit te kan bereik, is molekulêre merkers noodsaaklik. In hierdie studie is In voorlopige AFLP merker vir die blaarroesweerstandgeen gegenereer deur van gebulkte DNA monsters gebruik te maak. Die AFLP-merker is deur die S12/M14 en S12/M44 priemstukkombinasies gegenereer. Bevestigingsstudies in drie verskillende agtergronde as dié waaruit die merker ontwikkel is, het aangedui dat verskeie gevalle van rekombinasie tussen die merker en die geen voorgekom het, wat die noodsaaklikheid van In koppelingstudie benadruk. Indien dit sou blyk dat die koppelingsafstand aanvaarbaar is, kan die merker bruikbaar wees, aangesien dit in vyf verskillende koringagtergronde polimorfies was. Die koppelingsafstand word ook benodig voordat In intensiewe poging aangewend kan word om die merker te kloon. Dit sal die omskakeling van die AFLP-band na In meer gebruikersvriendelike STS merker moontlik maak.
Dissertation (M.Sc.Agric. (Plant Sciences))--University of the Free State, 2002
Keywords: Leaf rust resistance; Gene pyramiding; Wild relatives; Seedling resistance genes; Adult plant resistance genes; Lr34; Durability; Molecular marker technology; AFLP; Wheat -- Breeding; Wheat -- Disease and pest resistance; Puccinia triticina